Pengaruh Pemberian Aloe Vera Pada Pasien Luka Bakar - Andri Nugraha (Jurnal Medika Cendikia, 2015)
Burn injury give some effects, there are death, disabilities, loss of confidence and the high cost of healing. Burn injury patient needs treatment conducted directly to return the skin function. Therefore, aloe vera can be used as an inexpensive alternative treatment. Aims of the study: This literature search aimed to analyzethe results ofstudythat focuses oneffects ofthe use ofaloeveraforthe healing of burn injury. Method of the study:This study use literature review method ofnine electronic journal andthe keywords used are aloe vera, burn injury, management burn injury and therapy. Result of study:Aloeverahas a shapesuch asa triangle with tubular yellow flowers, fleshy leaveswithjagged edges, a lot of seeds and has a length of 30-50 cm and width 10 cm. Aloe vera given to treat first and second degree burn injury patients. Burn injuries were treated by aloe vera can heal faster and epithelializationof skin tissue because aloe vera contains antiseptic,anti-inflammatory and increase granulation tissue. Conclusions: aloe verais possible to heal first and second degree of burn injury because aloe vera can improve thegranulationtissue, antisepticandanti-inflammatory.